1st IWA international symposium on water and wastewater technologies in ancient civilizations : under the aegis of EU, EUREAU, FAO, UNESCO, and Assoc. of Municipalities - Αγγελάκης, Ανδρέας Ν.; Κουτσογιάννης, Δημήτριος; Κουτσογιάννης, Δημήτρης (National Foundation for Agricultural Research, 2006)
Symposium Preprint Book: Introductory Themes, From Mythology to Water Science, Water Resources Managemant in the Ancient World, Stormwater and Sanitary Technologies, Water Resources Technologies (Aqueducts, Cisterns, Dams, Qanats and Karez, and Foggaraw), Water Uses (Supply and Irrigation), Old Influences in Modern Water Technologies, Short Papers.